Educação dos estudantes com deficiência no contexto das escolas em tempo integral do município de Sorocaba. - Belarmino, Maria Hildelânia Nascimento (2024)
Full-Time Schooling and Special Education have taken on a prominent role in educational policies. In light of this, the present study poses the following question: How do the policy guidelines for Full-Time Schooling and Special Education affect the schooling of students with disabilities? Considering the importance of intersecting these policies, the main objective of this research was to analyze the guidelines related to Full-Time Schooling and Special Education policies from an inclusive perspective, within the context of municipal schools in Sorocaba. To achieve this, the following specific objectives were established: a) To understand the perceptions of school administrators regarding Special Education in Full-Time Schools within Sorocaba's municipal network; b) To identify the main challenges and strategies for supporting students with disabilities in the schools under study; c) To examine how the educational services for students with disabilities are implemented and the conditions for their schooling in Full-Time Schools in the municipality. The study employed Stephen J. Ball's policy cycle as an analytical framework and included bibliographic and documentary research, as well as interviews with administrators from Full-Time Elementary Schools in Sorocaba, São Paulo State. The analyses revealed that Special Education in Full-Time Schools is shaped by ongoing, limited, and restricted adaptations. The findings highlighted a fragmentation between Full-Time Schooling and Special Education policies, which are conceived in a sectoral manner and function in a disjointed way. Considering both the objective and subjective conditions, it was observed that these policies, in their contexts of influence and text production, do not align with their implementation in practice. The assistentialist approach that characterizes these policies has implications for practical contexts and raises critical questions about the social role of schools and the contradictions surrounding the (lack of) schooling of students with disabilities. It is concluded that both Full-Time Schooling and Special Education policies possess compensatory and remedial characteristics, reflecting the capitalist production model of schooling. This model seeks to regulate the process of knowledge socialization through the assistentialist nature of public schools.